Pengaruh Model Cooperative Project Based Learning Terhadap Hasil Belajar Siswa Pada Materi Teori Atom: Studi PTK Pada Kelas X-B Di SMA Negeri 2 Tondano - Laleno, Desnalia; Tuerah, Jeanne Maria; Palilingan, Septiany Ch. (General Chemistry Journal, 2025)
This study aims to improve student learning outcomes in atomic theory material through the application of cooperative project based learning learning models. The cooperative project-based learning model is learning that integrates project-based learning implemented with cooperative learning strategies. The research conducted was Classroom Action Research (PTK) which was conducted in 2 cycles, where each cycle consisted of planning, action, observation, and reflection stages. The research subjects were all students of class X-B at SMA Negeri 2 Tondano, with a total of 20 students consisting of 12 female students and 8 male students. Data collection techniques were carried out through observation and written tests. Cycle I, the percentage of classical mastery of students is 85%. Cycle II the percentage of students’ mastery classically becomes 100%. There was an increase in individual learning outcomes, with 17 students who completed learning in cycle I to 20 students who completed learning in cycle II. The results showed that the cooperative learning model based on project learning on atomic theory material improved student learning outcomes.